Sejarah Pembinaan Hukum Islam di Enam Periode - Husaeni, Benies; Drihestyawati, Elenita; Lesiani, Lesi (STAI Denpasar Bali, 2022)
The presence of Islam on earth does not only regulate human relations with the Creator, through worship or rituals of prayer, fasting, pilgrimage and so on. However, Islam also regulates the relationship between humans and humans or humans and the natural environment. The content of Islamic teachings does not only discuss one aspect, but also discusses various aspects, such as theology, philosophy, Sufism, history, Islamic law, Islamic medicine, economics, social and political affairs, Islamic psychology and so on. This research aims to show the relationship between Islam and various aspects of human life, as well as explaining the spirit in the form of moral messages and values ​​contained in various branches of Islamic knowledge. So that it can respond to various new paradigms and the emergence of new philosophies and ideologies. Then the research method used is the descriptive analysis method, namely explaining and describing the history of the development of Islamic law in six periods by referring to sources contained in the Koran, Sunnah, the thoughts of ulama and Islamic researchers. The results of this research show that each period has special characteristics in the social, political and cultural conditions for Muslims, which will have a big influence on the ijtihad and fatwas that have come to this day. Of the six periods, the development of law during the life of the Prophet Muhammad s.a.w is the main point that every faqih explains and relies on. then legal development during the great friend's time. This period ended with the end of Khulafaur Rasyidin r.a. Legal formation during the childhood of friends and tabi'in who were equal to them in their goodness. This period ended with the end of the first century of the Hijriyah or a little after that. Legal development during the fiqh era had become a branch of science. The development of law at a time which included problems originating from the priests, and the emergence of large essays (books) and many problems. Finally, legal guidance during the taqlid period alone. The period after that (period V) until now.